2(x+3)+3=2x+7

Simple and best practice solution for 2(x+3)+3=2x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+3)+3=2x+7 equation:


Simplifying
2(x + 3) + 3 = 2x + 7

Reorder the terms:
2(3 + x) + 3 = 2x + 7
(3 * 2 + x * 2) + 3 = 2x + 7
(6 + 2x) + 3 = 2x + 7

Reorder the terms:
6 + 3 + 2x = 2x + 7

Combine like terms: 6 + 3 = 9
9 + 2x = 2x + 7

Reorder the terms:
9 + 2x = 7 + 2x

Add '-2x' to each side of the equation.
9 + 2x + -2x = 7 + 2x + -2x

Combine like terms: 2x + -2x = 0
9 + 0 = 7 + 2x + -2x
9 = 7 + 2x + -2x

Combine like terms: 2x + -2x = 0
9 = 7 + 0
9 = 7

Solving
9 = 7

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 5x^3(3x^2-3x+5)= | | -6(3+r)=12 | | 2x-1=5x+4 | | 5x-9+6x=-31 | | C=40-2.5r | | x^2+6x*8=0 | | -6m^2=-21 | | X-47=187 | | 5(x-3)-2x=21 | | V=8(1) | | -5p+3=23 | | 13(n+6)= | | 2/3•3.14•9•20 | | X-47=137 | | 4/6/8 | | (2/3)^3x-2*(4/9)^x-2 | | Logx(-8-6x)=2 | | (4x+2)=(x-6) | | -9k-8+7k=-35 | | 2m+3=3m | | 1-sin^2(4x)=0 | | Cos(45-X)+cos(45+X)= | | x(2x-4)=63 | | 4x=3x-17 | | =(2x+1)(3x-2) | | 4d+3e-2d-4-1= | | n+5=7n-4 | | (2x-3)(7x+4)= | | x=28/14 | | 481=(7.6-11.3n) | | 10log(3x+5)=20 | | -34=9(8d+6) |

Equations solver categories